Pengaruh Pelatihan dan Kompensasi terhadap Kinerja Karyawan Pada PTSpinmill Indah Industry Tangerang - Dani Kurniawan; Mukhaer Pakkanna (Indonesian Journal of Economics Application (IJEA), 2021)
The problem that exists in the company today is about training. Many employees do not respond to existing activity in the company. Therefore, the lack of interest in training is a problem that enterprises in the future must address. Based on this description, this study aims to analyze the effect of exercise and compensation on employee performance at PT Spinmill Indah Industry Tangerang. This study used a saturated sampling technique involving a sample of 65 employee respondents. The Data Analysis Technique Used in This Research Is Multiple Regression Analysis and Correlation Test with SPSS Version 20 software. The results showed that the correlation value was 94.1 percent. The Adjusted R Square Determination Coefficient valueis 88.6 percent, which means that all independent variables, namely training and compensation, have an enormous contribution together.